The growing prominence of Turkey in the global sukuk market: an overview - Kayadibi, Saim; Tunc, Irfan; Abdul Wahab, Abdul Hamid; Kayadibi, Omer (2014)
Recent developments have shown that sukuk (Islamic bond) is one of the most noteworthy driving forces behind the growth of the Islamic capital market and Islamic finance as a whole. Unlike conventional bonds, sukuk offers the investor ownership of tangible assets, usufruct of an asset, or sometimes ownership of certain projects or investment activities. With the purpose of obtaining the needed financing through the Islamic capital market for operations, several organizations around the globe, especially in Southeast Asia and the Middle East, utilize sukuk as the Islamic financial instrument. While countries in the Southeast Asia and the Middle East are leading the sukuk market, Turkey is currently one of the most promising markets for sukuk worldwide. Going forward with this, the present study aims at giving a comprehensive overview about the development of sukuk and its opportunity for growth in Turkey. It also gives an account of the legal and regulatory issues pertaining to the Turkey sukuk. In general, the study is an attempt to create more awareness about the developments in sukuk and the recent active role Turkey plays in the sukuk market. Keywords: Islamic finance, Sukuk (Islamic bond), Shari’ah, Turkey, legislation JEL Classification: G 12, G 14, G 18